The effects of diabetes on male sexual function. - Fairburn, C; McCulloch, D; Wu, F (1982)
Diabetic men are prone to a variety of sexual problems. It is probable that most of these sexual difficulties are the result of a progressive physical disorder upon which a psychological reaction is superimposed. Assessment needs to take account of both the physical and psychological components of the problem. The aim of management is to help the patient and his partner enjoy sexual function to the full within whatever limits are set by irreversible factors. Management therefore involves correcting potentially reversible physical and psychological factors, and helping the patient and his partner adapt to the remaining irreversible changes in sexual function. Using this approach it may be possible to improve the prognosis of what in the past has been dismissed as an intractable clinical problem.